A Fault-Tolerant Control Framework for DFIG-Based Wind Energy Conversion Systems in a Hybrid Wind/PV Microgrid - Musarrat, Md Nafiz; Fekih, Afef (IEEE journal of emerging and selected topics in power electronics, 2021)
This article proposes a fault-tolerant control framework for a doubly fed induction generator (DFIG)-based wind energy conversion system (WECS) in a hybrid wind/photovoltaic system (PV) microgrid structure. It implements a fractional-order sliding mode control (SMC) for the DFIG converters to mitigate the grid faults and ensure robustness against mismatched uncertainties. It also includes a shared reactive power support strategy where both the WECS and PV system participate in providing the necessary reactive current by utilizing their converters as STATCOM. The proposed approach is validated using a wind/PV system installed in a feeder of a test microgrid system subject to short-term unbalanced grid voltage faults and mismatched disturbances. Its performance is further compared to that of a standard SMC-based approach. The obtained results show that the proposed framework improved the dynamic stability of the DC voltage and enabled grid support during both symmetrical and asymmetrical grid faults. Providing fast and robust control of the converters, ensuring compliance with the new grid codes and avoiding the activations of the crowbar system are among the positive features of the proposed framework.